Assessment of Levels of Disability in Children Following Post-Meningitis Sequelae: A Hospital-Based Cross-Sectional Study: Assessment of Levels of Disability in Children Following Post-Meningitis Sequelae - Nawaz, Sajal Rehman; Ahmad, Sarfaraz; Shabbir, Maida; Bari, Tayyaba; Gardezi, Sara Hussain; Zainab, .; Zobia, .; Rehman, Zoha (Pakistan Journal of Health Sciences, 2025)
Meningitis is a globally rampant disease, particularly affecting children, and often results in a series of debilitating neuro-physiological and cognitive impairments. These outcomes are collectively classified as post-meningitis sequelae in the pediatric population. Objectives: To assess the levels of disability among children following post-meningitis sequelae. Methods: A descriptive cross-sectional study was conducted on 144 children (aged 3–10 years) with post-meningitis sequelae at The Children’s Hospital, Lahore. Participants were selected using non-probability purposive sampling. Functional outcomes were assessed using a modified Pediatric Glasgow Outcome Scale – Extended (Peds-GOSE). Data were analyzed using SPSS version 26.0. Frequencies and percentages were calculated, and chi-square tests were applied to determine associations between demographic variables and disability levels. Results: Out of 144 children, 8% were in a vegetative state (Peds-GOSE 7), 36% had Lower Severe Disability (Peds-GOSE 6), 23% had Upper Severe Disability (Peds-GOSE 5), 17% had Lower Moderate Disability (Peds-GOSE 4), and 6% had Upper Moderate Disability (Peds-GOSE 3). Only 35% showed good recovery (Peds-GOSE 1–2). Overall, 65% experienced unfavorable outcomes (Peds-GOSE 3–7). A statistically significant association was found between age and disability level (χ² = 63.713, df = 12, p<0.001). Conclusion: The majority of children with post-meningitis sequelae demonstrated unfavorable outcomes, with 65.3% falling into moderate to severe disability categories. Lower Severe Disability (25%) was most common, while only 18.8% achieved complete recovery. Younger age was significantly associated with greater disability severity (p<0.001), indicating increased vulnerability in early childhood.